Rice Soluble Starch Synthase I: Allelic Variation, Expression, Function, and Interaction With Waxy - Li, Qianfeng; Liu, Xinyan; Zhang, Changquan; Jiang, Li; Jiang, Meiyan; Zhong, Min; Fan, Xiaolei; Gu, Minghong; Liu, Qiaoquan (Frontiers in Plant Science, 2018)
Starch, composed of amylose and amylopectin, is the key determinant of rice quality. Amylose is regulated by the Waxy (Wx) gene, while amylopectin is coordinated by various enzymes, including eight soluble starch synthases (SSS), of which SSSI accounts for 70% of total SSS activity in cereal endosperm. Although great progress has been made on understanding SSSI gene expression and function, allelic variation and its effects on gene expression, rice physicochemical properties and qualities, and interactions with the Wx gene remain unclear. Herein, SSSI nucleotide polymorphisms were analyzed in 165 rice varieties using five distinct molecular markers, three of which reside in the SSSI promoter and might account for higher expression of the SSSIi allele in indica than SSSIj in japonica subspecies. The results of SSSI promoter- Beta-Glucuronidase (GUS) analysis were consistent with the expression results. Moreover, analysis of near isogenic lines (NIL) in the Nipponbare (Nip) background showed that Nip(SSSIi) and Nip(SSSIj) differed in their thermal properties, gel consistency (GC) and granule crystal structure. Knockdown of SSSI expression using SSSI-RNAi in both japonica and indica backgrounds caused consistent changes in most tested physicochemical characteristics except GC. Moreover, taste value analysis showed that introduction of the indica SSSI allele or knockdown of SSSI expression in japonica cultivars significantly reduced the comprehensive taste value, consistent with the superior taste of japonica vs. indica. Furthermore, to test the potential interaction between SSSI and different Wx alleles, three NILs within the Wx locus were generated in the indica Longtefu (LTF) background, designated as LTF (Wxa), LTF (Wxb) and LTF (wx). The SSSI-RNAi construct was also introduced into these NILs, and physiochemical analysis confirmed that knockdown of SSSI significantly increased the rice apparent amylose content (AAC) only in the Wxa and Wxb background, and led to different changes in GC in the NILs. Therefore, the effect of SSSI variation on rice quality also depends on its crosstalk with other factors, especially the Wx gene. These findings provide fundamental knowledge for future breeding of rice with premium eating and cooking qualities.